2023
DOI: 10.7759/cureus.36637
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge of and Attitude Toward Oral Cancer Among the Outpatient Population in a Tertiary Care Rural Hospital

Abstract: IntroductionLack of knowledge and awareness about oral cancer and its risk factors and negligence of the early warning signs play a crucial role in raising the incidence of the disease. Therefore, the aim of this present study is to assess the awareness of oral cancer among the local population regarding the prevalence, etiology, early signs of oral cancer, and treatment options available for the same. Materials and methodsThe study was approved by the institutional ethics committee. A cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The misconception about oral cancer being contagious, as addressed in our study, is consistent with the observations made by Biswas (2014), who noted misconceptions related to oral cancer transmission in their research [29]. In terms of perceptions about the treatability of oral cancer, our study's results differ from the observations of Anirudh et al (2023) who found a higher percentage of participants believing in the treatability of oral cancer [30]. Our study's findings on the potential for dependence and addiction resulting from SLT consumption (63.2%) resonate with the conclusions drawn by Salvi et al (2019) who similarly highlighted the risks of dependence associated with SLT use [31].…”
Section: Discussionsupporting
confidence: 90%
“…The misconception about oral cancer being contagious, as addressed in our study, is consistent with the observations made by Biswas (2014), who noted misconceptions related to oral cancer transmission in their research [29]. In terms of perceptions about the treatability of oral cancer, our study's results differ from the observations of Anirudh et al (2023) who found a higher percentage of participants believing in the treatability of oral cancer [30]. Our study's findings on the potential for dependence and addiction resulting from SLT consumption (63.2%) resonate with the conclusions drawn by Salvi et al (2019) who similarly highlighted the risks of dependence associated with SLT use [31].…”
Section: Discussionsupporting
confidence: 90%